The game as a didactic object in the teaching of mathematics: a case study at the Manuel German Cuello Gutiérrez Educational Institution in the city of Valledupar - Solano, César Augusto Téllez; Mendoza, Héctor Luis Paz; Ortiz, Yeferson Jesús Barrera; Peralta, Keylin Karolina Ciro; Gelvez, Yuneidis Adriana Alvarado (Journal of Ecohumanism, 2024)
In this article, the authors propose a series of games, aligned with the secondary education curriculum, which is part of a master’s and undergraduate thesis at the Popular University of Cesar, which sought to determine how to introduce the game in the teaching of mathematics. The main objective of the article is to identify the potentialities of games in the development of mathematics classes, so it is structured in two parts; The first two chapters introduce what the game is about, the benefits it brings, etc. While the remaining chapters exemplify the use of play in the different stages of mathematics learning. There are various approaches or pedagogical trends considered: the creation or modification of materials by teachers; the development of analytical thinking; the active role of students; as well as the interest of the mathematics games presented and their playful role that favors the interest and attention of the students. All these approaches converge towards a single purpose, the development of logical-mathematical thinking through motivating and attractive situations for students. Mathematical games are activities that encourage students to make decisions, based on calculation, verification or reflection in their own environment and that start after the participation of the same, personal progress, fun and practical experience.